GIBRAN RAKABUMING RAKA'S RHETORIC IN THE 2024 CAWAPRES DEBATE IN A STUDY OF ARISTOTLE'S RHETORIC THEORY - Rina Raflina; Marlinda Irwanti Poernomo (International Journal of Social Science, 2025)
This research wants to know phronesis (intellectual), arate (quality), eunonia (good intentions), namely the elements of ethos, as well as pathos and logos found in Gibran Rakabuming Raka's rhetoric in the 2024 cawapress debate. This research is qualitative research using a content analysis approach. Content analysis is a systematic technique for analyzing message content and characterizing messages. Data collection in this research was through interviews with key informants, namely the audience and the Parabowo-Gibran success team as well as YouTube videos of the 2024 cawapres debate carried out by the Indonesian Broadcasting Commission (KPU). The theory used in this research is Aristotle's rhetorical theory which contains elements of ethos, phatos and logos. The results of interviews with informants (audience) in this research found that Gibran Rakabuming Raka has a unique character, straightforward, no nonsense, calm, rational, sharp, an open young man (ethos).